Simplify with assumptions

*To*: mathgroup at smc.vnet.net*Subject*: [mg32409] Simplify with assumptions*From*: "Dave Snead" <dsnead6 at charter.net>*Date*: Sat, 19 Jan 2002 01:16:51 -0500 (EST)*Sender*: owner-wri-mathgroup at wolfram.com

Using Mathematic 4.1, Why won't the 2nd expression simplify? Simplify[1 - c^2, s^2 + c^2 == 1] gives s^2 But Simplify[1 - s^2, s^2 + c^2 == 1] gives 1 - s^2 Why doesn't this 2nd expression yield c^2? The leaf count of both s^2 and c^2 are 3. While the leaf count for both 1 - s^2 and 1 - c^2 are 7.